Comparative Analysis of CAMELS and RGEC Methods in Assessing Banking Resilience in Indonesia - Cantika Salsabila Pratiwi; Wisudanto - - (Jurnal Studi Manajemen dan Bisnis, 2026)
Purpose: This study aims to examine the effectiveness of the CAMELS and RGEC frameworks in assessing banking resilience in Indonesia amid increasing economic uncertainty. The study addresses the question of which framework provides a better explanation of banking resilience under conditions characterized by exchange rate volatility, inflationary pressures, and monetary tightening policies.Design/methodology/approach: This study employs a quantitative research design using panel data regression analysis. The sample consists of commercial banks listed on the Indonesia Stock Exchange during the period 2020–2025. The CAMELS framework is represented by Capital, Asset Quality, Management, Earnings, Liquidity, and Sensitivity to Market Risk, while the RGEC framework comprises Risk Profile, Good Corporate Governance, Earnings, and Capital. Banking resilience is measured using Return on Assets (ROA) as an indicator of financial performance and stability.Findings: The study is expected to identify the relative effectiveness of the CAMELS and RGEC frameworks in explaining banking resilience and determining which framework provides a more comprehensive assessment of bank soundness under uncertain economic conditions.Research limitations/implications: The study is limited to commercial banks listed on the Indonesia Stock Exchange and may not fully capture the conditions of non-listed banks. Future research may expand the sample scope to include regional or international banking institutions and consider additional measures of banking resilience.Practical implications: The findings are expected to provide useful insights for bank management, investors, and regulators in evaluating bank performance, managing risks, and strengthening financial stabilityOriginality/value: This study contributes to the banking and financial stability literature by providing a comparative analysis of the CAMELS and RGEC frameworks in assessing banking resilience during a period of heightened economic uncertainty in Indonesia.